PELATIHAN PENGELOLAAN HOMESTAY SEBAGAI UPAYA PERCEPATAN PENGEMBANGAN DESA WISATA MEKAR SARI, LOMBOK TENGAH - Ihyana Hulfa; Nur Afiah; Siti Hamdiah Rojabi; Rishan Adha (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Tourism is currently a strategic sector in supporting economic and social development, especially in rural areas. One of the emerging approaches is the development of tourism villages based on community participation. Homestays as a form of community accommodation have an important role in providing authentic tourism experiences and supporting the welfare of villagers. However, in Mekar Sari Tourism Village, Central Lombok, the quality of homestay management still faces challenges, such as low service standards, limited facilities, and lack of innovation in services. In response to these conditions, this service activity was carried out through intensive training aimed at increasing the capacity of homestay managers in aspects of management, excellent service, and service development based on local potential. The training method was conducted in a participatory manner through interactive lectures, practical demonstrations, group discussions, and reflections. The results showed an increase in participants' understanding of the importance of service standards and the emergence of additional service initiatives such as cooking classes and cultural tours. This activity not only provides an initial impact on strengthening community capacity, but also strengthens collective awareness in building a sustainable and competitive tourism village.